Intelligent controller based power quality improvement of microgrid integration of photovoltaic power system using new cascade multilevel inverter - Gaddala Jayaraju; Gudapati Sambasiva Rao (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Now a day the power demand has a major problem for developing countries due to the growth of population, industries, IT companies and other needs. In this present situation the fossil fuel-based power generation alone does not support the consumer needs, poor power quality due to nonlinear function and very harmful for environment. The main objective of this paper is improving the power quality of grid connected photovoltaic power system through a new cascade H-bridge multilevel inverter. The proposed research work has been modelled and controlled by ANFIS intelligence in MATLAB simulation environment. The simulation results are analysed under various operating conditions for improve the performance of proposed system. Finally, the proposed system THD value of simulation results is compared with IEEE 1547 standard for prove the effectiveness of proposed research work.